Why Do People Act Like the Proverbial Ostrich? Investigating the Reasons That People Provide for Not Monitoring Their Goal Progress - Chang, Betty P. I.; Webb, Thomas L.; Benn, Yael (Frontiers in Psychology, 2017)
Two studies examined peoples’ reasons for not monitoring their progress toward their personal goals – a phenomenon that has been termed ‘the ostrich problem’ (Webb, Chang, & Benn, 2013). Study 1 used factor analysis to organize the reasons that people gave for not monitoring their goal progress, resulting in ten factors. The most strongly endorsed reasons were: a) that information on goal progress would demand a change in beliefs, or b) undesired action; c) that progress was poor, and d) that thinking about and / or working on the goal was associated with negative emotions. Study 2 adopted a prospective design and investigated whether the reasons identified in Study 1 predicted: a) the likelihood that participants would decline an opportunity to monitor their goal progress and b) the frequency with which participants monitored their goal progress. We found evidence that some of the most strongly endorsed reasons from Study 1 also predicted the avoidance of monitoring in Study 2; however, the belief that information about goal progress was likely to be inaccurate and not useful, and perceived control over goal attainment also reliably predicted the avoidance of monitoring. Taken together, the findings explain why people do not monitor their goal progress and point to potential avenues for intervention.